Impact of controlled atmosphere scheduling on strawberry and imported avocado fruit - Alamar, M. Carmen; Collings, Emma R.; Cools, Katherine; Terry, Leon A. (Elsevier, 2017)
British grown strawberry cv. Sonata and Chilean avocado cv. Hass were exposed to controlled atmospheres (CA) of 15 kPa CO2 + 5 kPa O2 (5 °C) and 10 kPa CO2 + 5 kPa O2 (5 or 20 °C), respectively, at early, middle or late stages during postharvest storage of avocados and at early and middle stages for strawberries. Real-time respiration rate (RR) was measured during CA storage and regular fruit sampling carried out to assess disease severity, objective colour, ethylene production and firmness. The automated in situ set-up used allowed continuous recordings of real-time respiration measurements without disruption to the CA environment. Cold stored strawberry fruit treated for 2.5 d with CA midway through the storage period were firmer and maintained a more vibrant colour despite bursts of increased RR. Furthermore, just 2.5 d of CA was sufficient to extend the shelf-life of strawberries (based on disease incidence) by a further 3 d, as compared to control. Irrespective of timing, RR of avocado stored at 20 °C was reduced while under CA environment; and early CA exposure maintained firmness yet increased the incidence of internal discolouration 7 d after removal from CA. At 5 °C, avocado skin colour and internal discolouration were positively affected by the mid CA treatment. These results are discussed in the context of the targeted use of CA, compared to control, for extending shelf-life, and reducing waste of these two different fruit produces. Furthermore, reducing the length of time required for CA application, which has not previously been explored in avocado or strawberries, would potentially be more energy efficient/cost effective.
Keywords: Respiration rate; Food quality; Food waste